Effect of bias on dielectric properties of SmCA∗ and SmC∗ phases of a perfluorinated antiferroelectric liquid crystal. (2016) - Ch. Dey, Kartick; Kumar Mandal, Pradip; Dabrowski, Roman
Abstract: A laterally fluorinated antiferroelectric liquid crystal was studied using bias dependent dielectric spectroscopy. The domain mode appeared when Goldstone mode of SmC∗ phase suppressed under bias. Critical frequency of domain mode increases with bias. It also suppresses under bias. In SmCA ∗, low frequency PL mode and high frequency PH mode were observed. Their ranges of critical frequencies are well separated. The weaker PL suppresses under bias, suggesting it arises from helical structure of antiferroelectric polarization. The critical field for suppression of PL increases with decrease of temperature. The stronger PH mode is almost bias independent, related to anti–phase fluctuation.